2018
DOI: 10.2147/ijn.s161319
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and transport of pullulan acetate nanoparticles in the BeWo b30 placental barrier cell model

Abstract: IntroductionNanomedicine has shown a great potential in perinatal medicine because of its characteristics of sustained, controlled release and targeting ability; on the other hand, it may also lead to unexpected toxicities such as embryotoxicity and even malformation after crossing the placental barrier, but data concerning transplacental transport are scarce. Pullulan acetate (PA) nanoparticles (NPs) are a promising nanocarrier derived from natural polysaccharide; however, their transplacental transport abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…NP derived from pullulan acetate are biocompatible and showed no cytotoxicity, neither in cell viability assays nor in animal tests. [ 132,133 ] Thus, they received interest as carrier for drug delivery purposes (see chapter 5.3.). Pullulan acetates have been further modified prior to the particle formation by derivatization with additional substituents to enhance drug encapsulation and/or release efficiency as well as to tailor the interaction with cells.…”
Section: Polysaccharide‐based Nanoparticlesmentioning
confidence: 99%
“…NP derived from pullulan acetate are biocompatible and showed no cytotoxicity, neither in cell viability assays nor in animal tests. [ 132,133 ] Thus, they received interest as carrier for drug delivery purposes (see chapter 5.3.). Pullulan acetates have been further modified prior to the particle formation by derivatization with additional substituents to enhance drug encapsulation and/or release efficiency as well as to tailor the interaction with cells.…”
Section: Polysaccharide‐based Nanoparticlesmentioning
confidence: 99%
“…One study has evaluated the internalization of gold nanoparticles on placental explants and revealed their translocation through the maternal-fetal barrier by clathrin-mediated endocytosis [ 33 ]. Tang et al have demonstrated that the main placental internalization mechanisms of negatively charged pullulan acetate nanoparticles by the BeWo cell line were pinocytosis and caveolae-mediated endocytosis [ 34 ]. More recently, the internalization of positively charged polymeric nanoparticles was related to dynamin dependent processes: mainly clathrin-mediated endocytosis [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…46 CFM allowed testing the efficacy of paclitaxel-loaded expansile NPs in a mesothelioma spheroid model, 47 the uptake and distribution of nanodiamonds in different cell lines and organ slices, 48 and the ability of Pullulan acetate NPs to pass the placental barrier in in vitro cell monolayers. 49 Furthermore, CFM was frequently used in combination with other imaging/microscopy techniques.…”
Section: Imaging Techniques Applied To In Vitro Modelsmentioning
confidence: 99%